1993
DOI: 10.1002/bjs.1800800633
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of C-reactive protein level, Ranson score and contrast-enhanced computed tomography in the prediction of septic complications of acute pancreatitis

Abstract: Randomized clinical trials of antibiotic prophylaxis in acute pancreatitis are now warranted in the light of recent evidence of pancreatic penetration of certain antibiotics at therapeutic minimal inhibitory concentrations. The aim of the present prospective clinical study was to investigate whether there are detectable risk factors for pancreatic sepsis in acute pancreatitis that would allow better selection of patients for inclusion in clinical trials. Fifty-nine consecutive patients with acute pancreatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
39
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 14 publications
5
39
0
2
Order By: Relevance
“…Our study confirmed the importance of pancreatic necrosis in determining disease severity as previously reported [4,[13][14][15][16][17][18]. Indeed, the risks of acute pancreatitis are most of all infectious complications that are directly linked to the presence of necrosis, a favourable environment to the development of bacteria [3,7,[19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirmed the importance of pancreatic necrosis in determining disease severity as previously reported [4,[13][14][15][16][17][18]. Indeed, the risks of acute pancreatitis are most of all infectious complications that are directly linked to the presence of necrosis, a favourable environment to the development of bacteria [3,7,[19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 90%
“…Multiple-factor biochemical criteria and different scoring system, such as Ranson's early prognostic signs and Acute Physiology and Chronic Health Evaluation (APACHE) have been used as prognostic indicators, but none has been proven ideal in clinical practice [1,6] . Contrast-enhanced CT is proven to be able to predict the severity of AP by scoring the degree of pancreatic tissue necrosis [36][37][38][39] , yet the main and widely accepted indication for dynamic CT in AP is clinical suspicion of life threatening local complication and to plan invasive intervention 2-3 weeks after admission for its costliness and X-ray exposure. Therefore, the candidate with AP for contrast-enhanced CT was about 14% [1] , and 11.5% patients receiving contrast-enhanced CT in our study was considered to be adequate.…”
Section: Discussionmentioning
confidence: 99%
“…Stratification of acute pancreatitis by severity has become necessary in order to find specific prognostic factors for SPI [14]. Some authors attempted to identify such specific factors, but their studies included patients with both mild A APACHE IIand severe pancreatitis [15]. In our opinion, these studies should only include patients with SAP because they are the only patients at risk of developing severe septic complications.…”
Section: Discussionmentioning
confidence: 99%
“…This way of ‘monitoring’ the risk of SPI allows early detection of septic complications and prompts the practice of an FNA to confirm the diagnosis. Prognostic factors obtained at the time of admission may predict the subsequent development of SPI [14, 15], but do not establish whether the risk of infection is increasing or not, therefore they do not indicate the right time to perform an FNA and do not speed up the diagnosis, which is the main objective to be attained. For similar reasons, other prognostic factors using variables determined only at two points during the evolution of an SAP do not provide conclusions applicable in clinical practice [17].…”
Section: Discussionmentioning
confidence: 99%